Relationship between Burnout and Mental-Illness-Related Stigma among Nonprofessional Occupational Mental Health Staff. (24th September 2019) - Mitake, Tomoe; Iwasaki, Shinichi; Deguchi, Yasuhiko; Nitta, Tomoko; Nogi, Yukako; Kadowaki, Aya; Niki, Akihiro; Inoue, Koki
Abstract : Background . Stigma related to mental illness can be an obstacle affecting the quality of life of people with mental illness. Although mental illness in the workplace is a public problem globally, few studies have investigated the effect of stigma on job-related problems such as burnout. Aim . This study aimed to clarify the association between mental-illness-related stigma and burnout among nonprofessional occupational mental health staff. Methods . In this cross-sectional study, nonprofessional occupational mental health staff's perceived mental-illness-related stigma was assessed using Link's Devaluation-Discrimination Scale, and their burnout was assessed using the Maslach Burnout Inventory. The association between stigma and burnout was analyzed by multiple linear regression analysis. Results . In total, 282 participants completed the questionnaire (response rate: 91.3%). We excluded 54 nurses from the analysis to examine strictly nonprofessional occupational mental health staff. Finally, 228 eligible respondents were surveyed. Multiple linear regression analysis revealed that mental-illness-related stigma was significantly associated with a high degree of depersonalization, which was one of the burnout dimensions. However, the impact of stigma over the depersonalization domain of burnout was minor. Conclusion . The results suggest that higher perceived mental-illness-related stigma is associated with more severe burnout. It is important to take measures against mental-illness-related stigma to avoid burnout among occupational mental health staff.